2018
DOI: 10.1155/2018/4149212
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of Plan‐Asymmetric Structures with Diaphragm Flexibility

Abstract: The seismic behavior of asymmetric structures with a flexible diaphragm was studied by conducting inelastic dynamic time-history analyses. Asymmetric structures with different configurations of mass, stiffness, and strength centers, in combination with a wide range of diaphragm flexibility, were evaluated. The behavior of structures was studied by considering three aspects: (1) effect of structural asymmetry on diaphragms deformation; (2) effect of diaphragm flexibility on demands of the lateral load-resisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Conversely, Eivani et al (2018) found remarkably greater shear deformation sensitivity in the diaphragms to the asymmetry and flexibility of the floor, which is why they considered the shear deformation component a clearer classification parameter. The conclusions of Eivani et al (2018) could be considered more reliable since they were based on more realistic models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Eivani et al (2018) found remarkably greater shear deformation sensitivity in the diaphragms to the asymmetry and flexibility of the floor, which is why they considered the shear deformation component a clearer classification parameter. The conclusions of Eivani et al (2018) could be considered more reliable since they were based on more realistic models.…”
Section: Introductionmentioning
confidence: 99%
“…Although the categories are accompanied by descriptions of behavior, these are very general and unreliable (Tena-Colunga 2015;Nakamura et al 2017b;Srisangeerthanan 2018). Recently, Nakamura et al (2017b) and Eivani et al (2018) proposed more refined and useful classifications based on the dominant characteristics of diaphragm deformation and on how incremental flexibility of the diaphragm affects wall responses. From parametric studies, in which the fundamental period of the diaphragm constitutes the basic parameter of classification, four categories of diaphragm are established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind turbines, towers, and foundations belong to high-rise structures, which need to withstand complex external environmental loads during their operation, and face problems such as structure vibration [6][7][8][9][10], soil-structure coupled vibration [11], seismic dynamic response [12,13], and vibration reduction control [14][15][16]. Offshore wind turbines, especially, have to face many challenges in complex ocean environments, including waves, currents, and erosion.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this assumption, distribution of inertial forces between lateral load-resisting elements (LLREs) of a structure is only dependent on its mass, stiffness and strength distribution. However, in many cases, fully rigid diaphragm assumption is not consistent with reality, and seismic diaphragms, especially in asymmetric-plan structures, can exhibit various degrees of flexibility [1][2][3][4]. Diaphragm flexibility can change the distribution of inertia forces between the LLREs and therefore can be the source of the difference between the results of the numerical analysis and the actual behaviour of the structure during the earthquakes.…”
Section: Introductionmentioning
confidence: 99%